Hollow plasmonic antennas for broadband SERS spectroscopy - Messina, Gabriele C.; Malerba, Mario; Zilio, Pierfrancesco; Miele, Ermanno; Dipalo, Michele; Ferrara, Lorenzo; De Angelis, Francesco (Beilstein Journal of Nanotechnology, 2015)
The chemical environment of cells is an extremely complex and multifaceted system that includes many types of proteins, lipids, nucleic acids and various other components. With the final aim of studying these components in detail, we have developed multiband plasmonic antennas, which are suitable for highly sensitive surface enhanced Raman spectroscopy (SERS) and are activated by a wide range of excitation wavelengths. The three-dimensional hollow nanoantennas were produced on an optical resist by a secondary electron lithography approach, generated by fast ion-beam milling on the polymer and then covered with silver in order to obtain plasmonic functionalities. The optical properties of these structures have been studied through finite element analysis simulations that demonstrated the presence of broadband absorption and multiband enhancement due to the unusual geometry of the antennas. The enhancement was confirmed by SERS measurements, which showed a large enhancement of the vibrational features both in the case of resonant excitation and out-of-resonance excitation. Such characteristics indicate that these structures are potential candidates for plasmonic enhancers in multifunctional opto-electronic biosensors.
Keywords: biosensing; multiband field enhancement; plasmonics; Raman spectroscopy; SERS

(untitled) - Kennedy, D. C.; Tay, L.-L.; Lyn, R. K.; Rouleau, Y.; Hulse, J.; Pezacki, J. P. (ACS Nano, 2009)

(untitled) - De Angelis, F.; Gentile, F.; Mecarini, F.; Das, G.; Moretti, M.; Candeloro, P.; Coluccio, M. L.; Cojoc, G.; Accardo, A.; Liberale, C.; Zaccaria, R. P.; Perozziello, G.; et al. (Nat. Photonics, 2011)

(untitled) - Huang, F. M.; Wilding, D.; Speed, J. D.; Russell, A. E.; Bartlett, P. N.; Baumberg, J. J. (Nano Lett., 2011)

(untitled) - Darvill, D.; Centeno, A.; Xie, F. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Miele, E.; Malerba, M.; Dipalo, M.; Rondanina, E.; Toma, A.; De Angelis, F. (Adv. Mater., 2014)

(untitled) - Homola, J. (Anal. Bioanal. Chem., 2003)

(untitled) - Valsecchi, C.; Brolo, A. G. (Langmuir, 2013)

(untitled) - Choi, Y.; Kang, T.; Lee, L. P. (Nano Lett., 2009)

(untitled) - Smith, E. A.; Corn, R. M. (Appl. Spectrosc., 2003)

(untitled) - De Angelis, F.; Das, G.; Candeloro, P.; Patrini, M.; Galli, M.; Bek, A.; Lazzarino, M.; Maksymov, I.; Liberale, C.; Andreani, L. C.; Di Fabrizio, E. (Nat. Nanotechnol., 2010)

(untitled) - Srituravanich, W.; Durant, S.; Lee, H.; Sun, C.; Zhang, X. (J. Vac. Sci. Technol., B, 2005)

(untitled) - Koenderink, A. F.; Hernández, J. V.; Robicheaux, F.; Noordam, L. D.; Polman, A. (Nano Lett., 2007)

(untitled) - Fang, Z.; Lin, C.; Ma, R.; Huang, S.; Zhu, X. (ACS Nano, 2010)

(untitled) - Yin, L.; Vlasko-Vlasov, V. K.; Pearson, J.; Hiller, J. M.; Hua, J.; Welp, U.; Brown, D. E.; Kimball, C. W. (Nano Lett., 2005)

(untitled) - Bergman, D. J.; Stockman, M. I. (Phys. Rev. Lett., 2003)

(untitled) - Noginov, M. A.; Zhu, G.; Belgrave, A. M.; Bakker, R.; Shalaev, V. M.; Narimanov, E. E.; Stout, S.; Herz, E.; Suteewong, T.; Wiesner, U. (Nature, 2009)

(untitled) - Holmgaard, T.; Gosciniak, J.; Bozhevolnyi, S. I. (Opt. Express, 2010)

(untitled) - Pile, D. F. P.; Gramotnev, D. K. (Opt. Lett., 2005)

(untitled) - Nazir, A.; Panaro, S.; Proietti Zaccaria, R.; Liberale, C.; De Angelis, F.; Toma, A. (Nano Lett., 2014)

(untitled) - Kneipp, K.; Kneipp, H.; Kneipp, J. (Acc. Chem. Res., 2006)

(untitled) - Notingher, I. (Sensors, 2007)

(untitled) - Li, M.; Xu, J.; Romero-Gonzalez, M.; Banwart, S. A.; Huang, W. E. (Curr. Opin. Biotechnol., 2012)

(untitled) - De Angelis, F.; Malerba, M.; Patrini, M.; Miele, E.; Das, G.; Toma, A.; Zaccaria, R. P.; Di Fabrizio, E. (Nano Lett., 2013)

(untitled) - Gittard, S. D.; Nguyen, A.; Obata, K.; Koroleva, A.; Narayan, R. J.; Chichkov, B. N. (Biomed. Opt. Express, 2011)

(untitled) - Messina, G. C.; Wagener, P.; Streubel, R.; De Giacomo, A.; Santagata, A.; Compagnini, G.; Barcikowski, S. (Phys. Chem. Chem. Phys., 2013)

(untitled) - Fang, Z.; Thongrattanasiri, S.; Schlather, A.; Liu, Z.; Ma, L.; Wang, Y.; Ajayan, P. M.; Nordlander, P.; Halas, N. J.; de Abajo, F. J. G. (ACS Nano, 2013)

(untitled) - Biagioni, P.; Huang, J.-S.; Hecht, B. (Rep. Prog. Phys., 2012)

(untitled) - Stratakis, E.; Kymakis, E. (Mater. Today, 2013)